Pengaruh Digitalisasi Terhadap Manajemen Perubahan pada UMKM d’Sruput Parak Laweh Kota Padang - Fatimah, Annissa; Syawalni, Mutia Riski; Utami, Jesica Naldi; Oktaviani, Wini (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
Digitalization has an important role in bringing change in various sectors, one of which is UMKM d'Sruput. This research aims to analyze the impact of digitalization on change management in UMKM d'Sruput Parak Laweh Padang City. The research method applied in this study is a descriptive qualitative approach through data collection carried out through interviews, observation and documentation. The results of this research show that digitalization can be the key to the success of UMKM in facing increasingly tight business competition. It can be concluded that digitalization has had a significant impact on change management in UMKM d'Sruput. UMKM d'Sruput need to realize the importance of digital transformation and start applying technology in various aspects, such as expanding market reach and improving the quality of customer service. However, there are several challenges faced in the digitalization process, such as a lack of competent human resources and limited internet access.